"Black Lives Matter" e la risignificazione della narrazione afroamericana nell’era digitale (Comparatismi, 2025)
This study investigates the narratological re-signification of African American activism in digital communication through a qualitative and theoretical analysis of the Instagram page of the Black Lives Matter movement. Drawing on the frameworks of Transmedial Narratology (Mittell, 2015) and Participatory Culture (Jenkins, 2006), the research explores how digital platforms enable the construction of new forms of political and social storytelling. The Instagram channel under analysis is interpreted as a transmedial text that merges visual, textual, and performative codes, where narrative strategies rooted in African American culture – such as call and response and repetition with a difference (Gates, 1988) – find renewed expressive space. The study does not rely on a quantitatively defined corpus, as it adopts a comparative and qualitative approach that treats the Instagram page as a “text” in the semiotic and cultural sense. In this light, the reflection offered here aims to provide a methodological and theoretical contribution for future research on Black aesthetics, digital activism, and social storytelling in contemporary media.
Keywords: Transmedial Narratology; Activism; Afroamerica; Identity; Digital Media